ANALISIS PENGARUH NPL DAN LDR TERHADAP NIM DENGAN ROA SEBAGAI INTERVENING, PENGARUH NPL TERHADAP NIM DENGAN CAR DAN ROA SEBAGAI INTERVENING, SERTA BOPO TERHADAP NIM BANK GO PUBLIC DI INDONESIA PERIODE 2011-2015 - Nugrahaning P, Sarwendah; Wahyudi, Sugeng (Diponegoro Journal of Management, 2016)
This study aims to examine the influence of CAR, NPL, LDR to NIM with ROA as Intervening variabel, the influence of BOPO and ROA to NIM, and the influence of NPL to NIM with CAR and ROA as Intervening Variable.The analysis method of this research is Path Analysis and Sobel Test. Total sample of this research is 23 commercial banks, which is obtain through purposive sampling. The data obtained from the official website of Otoritas Jasa Keuangan.The result of this research shows: NPL has negatif and not significant effect on CAR andÂ  has negatif and significant effect on ROA, however has negatif and significant effect on NIM. ROA significantly mediatin NPL to NIM. CAR has positive and not significant effect on ROA, and has positive and significant effect on NIM. LDR has positive and not significant effect on ROA, and positive and significant effect on NIM. ROA significantly mediating LDR to NIM. BOPO and ROA has positive and significant effect on NIM.